2020
DOI: 10.1530/vb-19-0031
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory fluid-induced mechanobiology in heart valves with parallels to the vasculature

Abstract: Forces generated by blood flow are known to contribute to cardiovascular development and remodeling. These hemodynamic forces induce molecular signals that are communicated from the endothelium to various cell types. The cardiovascular system consists of the heart and the vasculature, and together they deliver nutrients throughout the body. While heart valves and blood vessels experience different environmental forces and differ in morphology as well as cell types, they both can undergo pathological remodeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 124 publications
0
6
0
Order By: Relevance
“…In terms of valvular development, it has been found that elongation and thinning of the valves can be independently regulated by fluid shear stresses, tensile stresses, and chronic cyclical stretches through mechanotransduction programs [ 37 , 38 , 39 ]. For instance, as reviewed elsewhere [ 40 , 41 ], it has been suggested that the side of the semilunar valve that faces the aorta (arterial side) experiences oscillatory shear stress (in response to reversing flows), while the side that faces the ventricle experiences laminar shear stress (in response to unidirectional flow). Recently, using a combination of in vivo and in vitro assays in fetal mice and chick embryos, it was demonstrated that, on the arterial side of the valve, mechanotransduction of low oscillatory shear stress through canonical Wnt signaling resulted in increased endocardial cell BMP signaling and cellular proliferation, leading to elongation and growth of the semilunar valve on the arterial side [ 37 ].…”
Section: Flow-mediated Mechanisms Of Left Heart Developmentmentioning
confidence: 99%
“…In terms of valvular development, it has been found that elongation and thinning of the valves can be independently regulated by fluid shear stresses, tensile stresses, and chronic cyclical stretches through mechanotransduction programs [ 37 , 38 , 39 ]. For instance, as reviewed elsewhere [ 40 , 41 ], it has been suggested that the side of the semilunar valve that faces the aorta (arterial side) experiences oscillatory shear stress (in response to reversing flows), while the side that faces the ventricle experiences laminar shear stress (in response to unidirectional flow). Recently, using a combination of in vivo and in vitro assays in fetal mice and chick embryos, it was demonstrated that, on the arterial side of the valve, mechanotransduction of low oscillatory shear stress through canonical Wnt signaling resulted in increased endocardial cell BMP signaling and cellular proliferation, leading to elongation and growth of the semilunar valve on the arterial side [ 37 ].…”
Section: Flow-mediated Mechanisms Of Left Heart Developmentmentioning
confidence: 99%
“…The loss of water, which is a major component of the extracellular matrix and contributes to tissue viscoelasticity, is likely responsible for reduced viscous relaxation. Therefore, these compositional alterations observed could have functional consequences on the valves resulting in stiffer, less extensible, and less viscous [ 26 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: The Complex Nature Of Functional Mitral Regurgitationmentioning
confidence: 99%
“…The major complications are atrial fibrillation or flutter, pulmonary arterial hypertension and heart failure [69]. Epidemiological studies estimated that MVR occurs in up to 10% of the worldwide population [41].…”
Section: Introductionmentioning
confidence: 99%